Roxadustat: Not just for anemia - Zhu, Xiaoyu; Jiang, Lili; Wei, Xuejiao; Long, Mengtuan; Du, Yujun (Frontiers in Pharmacology, 2022)
Roxadustat is a recently approved hypoxia-inducible factor prolyl hydroxylase inhibitor that has demonstrated favorable safety and efficacy in the treatment of renal anemia. Recent studies found it also has potential for the treatment of other hypoxia-related diseases. Although clinical studies have not yet found significant adverse or off-target effects of roxadustat, clinicians must be vigilant about these possible effects. Hypoxia-inducible factor regulates the expression of many genes and physiological processes in response to a decreased level of oxygen, but its role in the pathogenesis of different diseases is complex and controversial. In addition to increasing the expression of hypoxia-inducible factor, roxadustat also has some effects that may be HIF-independent, indicating some potential off-target effects. This article reviews the pharmacological characteristics of roxadustat, its current status in the treatment of renal anemia, and its possible effects on other pathological mechanisms.